2017
DOI: 10.1139/cjp-2016-0848
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic analysis of CdCl2 doped PVA–PVP blend films

Abstract: Abstract:The changes in molecular chemical structure of polyvinyl alcohol (PVA) and polyvinyl pyrrolidone (PVP), caused by doping PVA-PVP blend with cadmium chloride (CdCl 2 ), have been studied using UV-Visible (UV-Vis) spectroscopy, Fourier Transform Raman spectroscopy and Fourier Transform Infrared (FTIR) spectroscopy. The formation of cadmium nano-structures and microstructures in CdCl 2 doped PVA-PVP blend has been visualized using Scanning Electron Microscopy (SEM), in the range of doping levels varying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…However, a strong absorption peak appears at the wavelength from 240 to 290 nm, which belongs to C-H bend peak of a vibrational structure. It is due to the dipole-dipole interaction between molecules [66], or n → π * transition, because of unsaturated (C=O) bond break, as reported earlier [67]. Compared with the pure PVA films and PVA/CQDs films, the transmittance of PVA/CNF films and PVA/CNF/CQDs films decreases with the addition of CNF (8 wt.%) into PVA-based film, showing that barrier property to light of PVA/CNF film improved by the introduction of CNF.…”
Section: Barrier Property To Light Of the Prepared Pva-based Filmssupporting
confidence: 62%
“…However, a strong absorption peak appears at the wavelength from 240 to 290 nm, which belongs to C-H bend peak of a vibrational structure. It is due to the dipole-dipole interaction between molecules [66], or n → π * transition, because of unsaturated (C=O) bond break, as reported earlier [67]. Compared with the pure PVA films and PVA/CQDs films, the transmittance of PVA/CNF films and PVA/CNF/CQDs films decreases with the addition of CNF (8 wt.%) into PVA-based film, showing that barrier property to light of PVA/CNF film improved by the introduction of CNF.…”
Section: Barrier Property To Light Of the Prepared Pva-based Filmssupporting
confidence: 62%
“…Lee et al [78] demonstrated that the reduction in transmittance percentage is an advantage for food packaging application. However, a strong absorption peak arrived in the wavelength range of 240 to 310 nm, which could be attributed to dipole-dipole interaction between molecules or n → π * transition, because of unsaturated C=O bond break as reported earlier [79,80]. The transparency and opacity of all the prepared films were calculated and shown in Fig.…”
Section: The Effect Of 7h4mc On Optical Properties Of Pva/omssupporting
confidence: 58%
“…Formation of charge transfer complexes modifies the band structure of the PVA-PVP blend, on adding CdCl 2 [55]. For 10.2 wt% of CdCl 2 in the PVA/PVAc-PVP blend, the sample is amorphous in nature, but contains micro-globules of dopant encapsulated by polymer molecules [56]. In the amorphous region, polymer chains are flexible and mobile, and hence, the dipoles can orient themselves easily with the applied field at low frequency.…”
Section: 2c Tangent Lossmentioning
confidence: 99%